How Natural Capital Approaches Can Support Sustainable Investments and Markets - White, Elizabeth M.; Rahill, Bilal; Gough, Mark; Spurgeon, James (International Finance Corporation, Washington, DC, 2020)
The world’s stocks of natural resources its natural capital and the rich ecosystem it provides support business and economies to the tune of forty-four trillion in economic value each year. Yet the enormous value of this natural capital has been neglected and largely invisible from private sector decision making. This has had an impact on nature’s capacity to continue providing the ecosystem services upon which businesses and society rely. Nature’s current decline, underpinned by unsustainable consumption and production patterns, population dynamics, deforestation, and land use change, is a clear risk to business, markets, and society. The way that businesses measure, value, relate to, and account for the interaction between nature and people must evolve, and quickly. Building markets that consider natural assets and the services they provide alongside financial assets can provide a new, insightful, and relevant way to address and manage serious environmental challenges, while building long-term sustainability and resiliency in the private sector. This note underscores the urgency of action and shares ways companies can use natural capital approaches to help maintain both nature and their ongoing role in advancing prosperity and development in emerging markets.